2012
DOI: 10.1007/s10570-012-9721-5
|View full text |Cite
|
Sign up to set email alerts
|

TEMPO-oxidized cellulose nanofiber films: effect of surface morphology on water resistance

Abstract: 2,2,6,6-Tetramethylpiperidine-1-oxyl radical (TEMPO)-oxidized cellulose nanofibers were prepared from two kraft pulps (Norway spruce and mixed eucalyptus) using the TEMPO/NaBr/NaClO system at pH 10 and 22°C. After reaction and mechanical treatment, the TEMPO-oxidized celluloses were used for preparation of self-standing films and coatings of laminate films on 50-lm-thick polyethylene terephthalate films. Characterization of the films was performed based on water contact angle measurements, laser profilometry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…Saito et al (2009) [44] also reported that TEMPO/NaClO/NaClO 2 system provides CNF with up to approximately 1.5 times higher tensile strength (312 MPa) compared to those CNF from TEMPO/ NaBr/NaClO, which was again attributed to the higher DP of the final CNF. Moreover, Rodionova et al (2012) [8] reported that the final refining and homogenization process results in significantly higher defects and shorter lengths for hardwood nanofibers compared to softwood nanofibers; so, the correspondent tensile strengths of the softwood nanofiber films were significantly higher than the strengths of the hardwood nanofiber films.…”
Section: Mechanicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Saito et al (2009) [44] also reported that TEMPO/NaClO/NaClO 2 system provides CNF with up to approximately 1.5 times higher tensile strength (312 MPa) compared to those CNF from TEMPO/ NaBr/NaClO, which was again attributed to the higher DP of the final CNF. Moreover, Rodionova et al (2012) [8] reported that the final refining and homogenization process results in significantly higher defects and shorter lengths for hardwood nanofibers compared to softwood nanofibers; so, the correspondent tensile strengths of the softwood nanofiber films were significantly higher than the strengths of the hardwood nanofiber films.…”
Section: Mechanicalmentioning
confidence: 99%
“…In aqueous environments, TEMPO catalyzes the conversion of carbohydrate primary alcohols to carboxylate (COO-) functional groups in the presence of a primary oxidizing agent, for example, sodium hypochlorite (NaOCl). In particular, wood fibers can be 2 Journal of Nanomaterials converted to individual nanofibers 3-4 nm wide with several microns length by TEMPO-mediated oxidation and successive mild disintegration in water [7,8]. During this reaction significant amounts of C6 carboxylate groups are selectively formed on each cellulose microfibril surface with minimum changes of the original crystallinity of the cellulosic material.…”
Section: Introductionmentioning
confidence: 99%
“…A rigid hydrogenbond network of cellulose nanofibrils governed by percolation might also form in the composite films (Zhou et al 2012). Figure 5 shows the contact angle (CA) change of a water droplet on the films with the increase of (Rodionova et al 2012a). The initial water contact angle of pure TOCNs film was 46.2°, consistent with the high hydrophilicity of the TOCNs film reported elsewhere (Fukuzumi et al 2009).…”
Section: Miscibilitymentioning
confidence: 99%
“…Cellulose nanofibrils (CNs) have attracted considerable attention in recent years due to their biodegradability, large surface area, high strength and high filmforming capacity (Rodionova et al 2012a). It is a highly reproducible and environmentally friendly nanomaterial (Fujisawa et al 2011) and has been used as the nano-fillers (Iwatake et al 2008), thin coating layers (Aulin and Strom 2013), and films (Song et al 2014) for many generic and cutting-edge products.…”
Section: Introductionmentioning
confidence: 99%
“…Casting is a time-consuming process, typically taking days or weeks. For example, Sehaqui et al (2010) reported that preparing 40-lmthick films with a diameter of 80 mm under atmospheric conditions starting with CNF concentration of 0.2 wt% took more than 120 h. To accelerate the processing, the castings are sometimes carried out with slight heating under vacuum (Spence et al 2010;Xhanari et al 2011;Rodionova et al 2012). A second popular and relatively fast method to produce CNF films involves the filtration of CNF solutions and drying the obtained hydrogels (Henriksson et al 2008;Qing et al 2013b).…”
Section: Introductionmentioning
confidence: 99%